Zirconia composite ceramic
By using zirconia composite ceramic composed of pentachromium triboride, Ce-TZP and Y-TZP, the problem of spontaneous phase transition of Y-TZP tetragonal phase zirconia ceramic in hydrothermal environment is solved, excellent anti-hydrothermal aging performance and high hardness are achieved, and its application range is expanded.
Patent Information
- Application Number
- CN202310546196.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-16
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-05-16
AI Technical Summary
The existing Y-TZP tetragonal phase zirconia ceramics will spontaneously transform into monoclinic phase under hydrothermal environments of 100 to 400°C, resulting in submicron cracks and surface roughness changes, limiting its application range.
The zirconia composite ceramic composed of 5~30 wt% pentachromium triboride, 5~15 wt% Ce-TZP and the remaining Y-TZP is adopted. Through the synergistic effect of the thermal expansion coefficient of pentachromium triboride and the compressive stress of tetragonal phase zirconia ceramic, the aging phase change of tetragonal phase zirconia ceramic in the hydrothermal environment is suppressed, and the surface hardness is improved.
It realizes the aging-resistant phase change performance of zirconia ceramics in hydrothermal environments, improves surface hardness and fracture toughness, and significantly expands the application range of zirconia ceramics.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the field of zirconia ceramics, and in particular to a zirconia composite ceramic. Background Art
[0002] Zirconia ceramics have three crystal phases: monoclinic, tetragonal and cubic. When the tetragonal phase transforms into the monoclinic phase, it is accompanied not only by energy consumption but also by a 3-5% volume expansion. Volume expansion leads to the generation of compressive stress. The synergistic effect of this energy consumption and the formation of compressive stress effectively hinders the expansion of cracks, thereby significantly improving the fracture toughness of zirconia ceramics, making tetragonal zirconia ceramics have the reputation of "ceramic steel".
[0003] Pure zirconia exists in the monoclinic phase below 1170℃, in the tetragonal phase between 1170 and 2370℃, and in the cubic phase above 2370℃. Therefore, in order to obtain tetragonal zirconia ceramics at room temperature, stabilizers are often added to zirconia ceramics so that the tetragonal phase can be maintained at room temperature. Common stabilizers include Y2O3, CeO2, MgO, etc. Among them, tetragonal zirconia ceramics stabilized by Y2O3 have been the most widely used due to their extremely high fracture strength and fracture toughness.
[0004] With the development of science and technology, people have further discovered that the existing Y-TZP tetragonal zirconia ceramics will spontaneously transform into a monoclinic phase in a hydrothermal environment of 100-400°C. This spontaneous phase change will not only cause submicron cracks in the zirconia ceramics, but also cause the surface roughness of the zirconia ceramics to change due to the 3-5% volume change associated with the phase change. This phenomenon limits the further application of 3Y-TZP tetragonal zirconia ceramics.
[0005] In order to solve this problem, researchers represented by CeramTec in Germany developed alumina-zirconia ceramics, in which zirconia is a minor component with a content of about 15wt%. It not only takes advantage of its phase change toughening, but also takes advantage of the pinning effect of the main component, the alumina matrix, to prevent the spontaneous phase change of zirconia in a hydrothermal environment. This idea has achieved certain results, but actual experience shows that the spontaneous phase change of zirconia still exists. In addition, compared with alumina ceramics, the surface hardness of zirconia ceramics is relatively low, which further hinders the application of zirconia ceramics in the industrial and medical industries. Summary of the invention
[0006] Technical problem to be solved: The purpose of the present invention is to provide a zirconia composite ceramic, which is composed of 5~30wt% pentachromium triboride, 5~15wt% Ce-TZP and the balance Y-TZP. The zirconia composite ceramic of the present invention not only has excellent hydrothermal aging resistance, but also has good surface hardness and fracture toughness, which significantly expands the application range of zirconia ceramics.
[0007] Technical solution: A zirconium oxide composite ceramic, which is composed of 5-30wt% pentachromium triboride, 5-15wt% Ce-TZP and the remainder Y-TZP.
[0008] Preferably, the composite ceramic consists of 5-20wt% pentachromium triboride, 5-15wt% Ce-TZP and the balance Y-TZP.
[0009] Preferably, the composite ceramic consists of 10-15wt% pentachromium triboride, 10-15wt% Ce-TZP and the balance Y-TZP.
[0010] Preferably, the composite ceramic consists of 12-15wt% pentachromium triboride, 12-15wt% Ce-TZP and the balance Y-TZP.
[0011] Preferably, the grain size of the pentachromium triboride is 1.5-3.5 µm, the grain size of Ce-TZP is 1.0-5.0 µm, and the grain size of Y-TZP is 0.4-0.8 µm.
[0012] Preferably, the grain size of the pentachromium triboride is 2.5-3.5 µm, the grain size of Ce-TZP is 1.0-3.0 µm, and the grain size of Y-TZP is 0.5-0.7 µm.
[0013] Beneficial effects: The present invention has the following advantages:
[0014] 1. The zirconium oxide composite ceramic of the present invention is composed of pentachromium triboride, Ce-TZP and Y-TZP. The thermal expansion coefficient of pentachromium triboride is about 13.7×10 -6 / ℃, the thermal expansion coefficient of tetragonal zirconia ceramics is about 10.5×10 -6 / ℃, during the sintering and cooling process, the composite ceramic formed by the two is subjected to tensile stress on the pentachromium triboride crystals and compressive stress on the tetragonal zirconia ceramics, which can well inhibit the aging phase transformation of the tetragonal zirconia ceramics in a hydrothermal environment. At the same time, the hardness of pentachromium triboride is high, and the surface hardness of the composite ceramic formed is better than that of simple tetragonal zirconia ceramics.
[0015] 2. The zirconia composite ceramic of the present invention is composed of pentachromium triboride, Ce-TZP and Y-TZP. The addition of Y-TZP and Ce-TZP makes up for the decrease in fracture toughness caused by the addition of Cr5B3. The zirconia composite ceramic of the present invention not only has excellent hydrothermal aging resistance, but also has good surface hardness and fracture toughness, which significantly expands the application range of zirconia ceramics.
[0016] In nature, hafnium (Hf) and zirconium elements exist in the form of solid solution and are difficult to separate, so in this application, "zirconium oxide (ZrO2)" contains ≤5wt% hafnium oxide.
[0017] In the present application, "Y-TZP" refers to a tetragonal zirconia ceramic containing 2-4 mol % Y2O3, and "Ce-TZP" refers to a tetragonal zirconia ceramic containing 10-12 mol % CeO2.
[0018] In the present application, "hydrothermal treatment" refers to exposure to water vapor at a temperature of 134°C and a pressure of 0.2 MPa in an autoclave.
[0019] In the present application, “vol%” refers to volume percentage, “wt%” refers to mass percentage, and “mol%” refers to molar percentage.
[0020] In the present application, X-ray diffraction analysis (abbreviated as "XRD", Cukα, 30KV, 15mA) is used to determine the crystalline phase content. Therefore, the obtained crystalline phase content refers to the crystalline phase content in the surface layer penetrated by the X-ray in the XRD analysis.
[0021] In the present application, room temperature refers to -20°C to 40°C.
[0022] In this application, the density of zirconia ceramics is measured using the water displacement method specified in GB / T 25995.
[0023] In the present application, the hardness of ceramics is measured using a Vickers hardness tester with a load of 5 kg.
[0024] In this application, the fracture toughness of ceramics was measured using the single-edge open beam (SENB) method with a specimen size of 3 mm × 4 mm × 24 mm, a span of 16 mm, a notch depth of 2 mm, and a notch width of 0.2 mm. DETAILED DESCRIPTION
[0025] The present invention will be further described below in conjunction with embodiments, which are explanations of the present invention and are not limited to the following embodiments:
[0026] Example 1 Preparation of zirconium oxide composite ceramic 1
[0027] The commercially available Y-TZP powder containing 3 mol% yttrium oxide and a primary particle size of 90 nm, the commercially available Ce-TZP powder containing 12 mol% cerium oxide and a primary particle size of 85 nm, and the commercially available Cr5B3 powder with a primary particle size of 57 nm were added to anhydrous ethanol in a weight ratio of 90:5:5, mixed evenly on a ball mill, then poured on a white porcelain plate, and dried in an oven at 100°C. The dried mixed powder was spray granulated to obtain 500 g of granulated powder with an average particle size of 60 µm, which was isostatically pressed under a pressure of 200 MPa, and then heated to 1550°C at a rate of 2°C / min in a high-temperature furnace in an air atmosphere and kept warm for 2 hours. After cooling to 600°C at a rate of 3°C / min and furnace cooling to room temperature, a zirconium oxide composite ceramic with a density of 98.4% of the theoretical density was obtained.
[0028] X-ray diffraction analysis of the zirconia composite ceramic showed that it was composed of zirconia crystal phase and Cr5B3 crystal phase, in which the content of monoclinic zirconia and tetragonal zirconia in the zirconia crystal phase was 2.1vol% and 97.9vol%, respectively. Analysis under SEM (scanning electron microscope) showed that the grain size of Y-TZP in the zirconia composite ceramic was 0.65µm, the grain size of Ce-TZP was 2.5µm, and the grain size of Cr5B3 was 2.4µm.
[0029] After analysis, the hardness of the ceramic is 10.9Gpa and the fracture toughness is 8.1Mpa.m 1 / 2 After the zirconia composite ceramic was hydrothermally treated at 134°C in water vapor at a pressure of 0.2 MPa for 20 h, the crystal phase composition of the zirconia composite ceramic was analyzed by X-ray diffraction, and it was found that it was composed of zirconia crystal phase and Cr5B3 crystal phase, wherein the content of monoclinic phase and tetragonal zirconia in the zirconia crystal phase was 40.5 vol% and 59.5 vol%, respectively.
[0030] Example 2 Preparation of zirconium oxide composite ceramic 2
[0031] The commercially available Y-TZP powder containing 3 mol% yttrium oxide and a primary particle size of 90nm, the commercially available Ce-TZP powder containing 12 mol% cerium oxide and a primary particle size of 85nm, and the commercially available Cr5B3 powder with a primary particle size of 57nm were added to anhydrous ethanol in a weight ratio of 80:15:5, mixed evenly on a ball mill, then poured on a white porcelain plate, and dried in an oven at 100°C. The dried mixed powder was spray granulated to obtain 500g of granulated powder with an average particle size of 60µm, which was isostatically pressed under a pressure of 200MPa, and then heated to 1550°C at a rate of 2°C / min in a high-temperature furnace in an air atmosphere and kept warm for 2h. After cooling to 600°C at a rate of 3°C / min and furnace cooling to room temperature, a zirconium oxide composite ceramic with a density of 98.3% of the theoretical density was obtained.
[0032] X-ray diffraction analysis of the zirconia composite ceramic showed that it was composed of zirconia crystal phase and Cr5B3 crystal phase, in which the contents of monoclinic and tetragonal zirconia in the zirconia crystal phase were 1.9 vol% and 98.1 vol%, respectively. Analysis under SEM (scanning electron microscope) showed that the grain size of Y-TZP, Ce-TZP and Cr5B3 in the zirconia composite ceramic was 0.63 µm, 2.4 µm and 2.5 µm, respectively.
[0033] After analysis, the hardness of the ceramic is 10.9Gpa and the fracture toughness is 8.6Mpa.m 1 / 2 After the zirconia composite ceramic was hydrothermally treated at 134°C in water vapor at a pressure of 0.2 MPa for 20 h, the crystal phase composition of the zirconia composite ceramic was analyzed by X-ray diffraction, and it was found that it was composed of zirconia crystal phase and Cr5B3 crystal phase, wherein the contents of monoclinic and tetragonal zirconia in the zirconia crystal phase were 38.0 vol% and 62.0 vol%, respectively.
[0034] Example 3 Preparation of zirconium oxide composite ceramic 3
[0035] The commercially available Y-TZP powder containing 3 mol% yttrium oxide and a primary particle size of 90nm, the commercially available Ce-TZP powder containing 12 mol% cerium oxide and a primary particle size of 85nm, and the commercially available Cr5B3 powder with a primary particle size of 57nm were added to anhydrous ethanol in a weight ratio of 80:5:15, mixed evenly on a ball mill, then poured on a white porcelain plate, and dried in an oven at 100°C. The dried mixed powder was spray granulated to obtain 500g of granulated powder with an average particle size of 60µm, which was isostatically pressed under a pressure of 200MPa, and then heated to 1550°C at a rate of 2°C / min in a high-temperature furnace in an air atmosphere and kept warm for 2h. After cooling to 600°C at a rate of 3°C / min and furnace cooling to room temperature, a zirconium oxide composite ceramic with a density of 98.4% of the theoretical density was obtained.
[0036] X-ray diffraction analysis of the zirconia composite ceramic showed that it was composed of zirconia crystal phase and Cr5B3 crystal phase, in which the contents of monoclinic and tetragonal zirconia in the zirconia crystal phase were 1.0 vol% and 99.0 vol%, respectively. Analysis under SEM (scanning electron microscope) showed that the grain size of Y-TZP in the zirconia composite ceramic was 0.65 µm, the grain size of Ce-TZP was 2.5 µm, and the grain size of Cr5B3 was 2.5 µm.
[0037] After analysis, the hardness of the ceramic is 11.7Gpa and the fracture toughness is 7.7Mpa.m 1 / 2 After the zirconia composite ceramic was hydrothermally treated at 134°C in water vapor at a pressure of 0.2 MPa for 20 h, the crystal phase composition of the zirconia composite ceramic was analyzed by X-ray diffraction, and it was found that it was composed of zirconia crystal phase and Cr5B3 crystal phase, wherein the contents of monoclinic and tetragonal zirconia in the zirconia crystal phase were 8.0 vol% and 92.0 vol%, respectively.
[0038] Example 4 Preparation of zirconium oxide composite ceramic 4
[0039] The commercially available Y-TZP powder containing 3 mol% yttrium oxide and a primary particle size of 90 nm, the commercially available Ce-TZP powder containing 12 mol% cerium oxide and a primary particle size of 85 nm, and the commercially available Cr5B3 powder with a primary particle size of 57 nm were added to anhydrous ethanol in a weight ratio of 80:10:10, mixed evenly on a ball mill, then poured on a white porcelain plate, and dried in an oven at 100°C. The dried mixed powder was spray granulated to obtain 500 g of granulated powder with an average particle size of 60 µm, which was isostatically pressed under a pressure of 200 MPa, and then heated to 1550°C at a rate of 2°C / min in a high-temperature furnace in an air atmosphere and kept warm for 2 hours, cooled to 600°C at a rate of 3°C / min, and furnace-cooled to room temperature to obtain a zirconium oxide composite ceramic with a density of 98.3% of the theoretical density.
[0040] X-ray diffraction analysis of the zirconia composite ceramic showed that it was composed of zirconia crystal phase and Cr5B3 crystal phase, in which the contents of monoclinic and tetragonal zirconia in the zirconia crystal phase were 1.0 vol% and 99.0 vol%, respectively. Analysis under SEM (scanning electron microscope) showed that the grain size of Y-TZP, Ce-TZP and Cr5B3 in the zirconia composite ceramic was 0.63 µm, 2.5 µm and 2.5 µm, respectively.
[0041] After analysis, the hardness of the ceramic is 11.2Gpa and the fracture toughness is 8.2Mpa.m 1 / 2 After the zirconium oxide composite ceramic was hydrothermally treated at 134°C in water vapor at a pressure of 0.2 MPa for 20 h, the crystal phase composition of the zirconium oxide composite ceramic was analyzed by X-ray diffraction, and it was found that it was composed of zirconium oxide crystal phase and Cr5B3 crystal phase, wherein the contents of monoclinic and tetragonal zirconium oxide in the zirconium oxide crystal phase were 10.2 vol% and 89.8 vol%, respectively.
[0042] Example 5 Preparation of zirconium oxide composite ceramic 5
[0043] The commercially available Y-TZP powder containing 3 mol% yttrium oxide and a primary particle size of 90 nm, the commercially available Ce-TZP powder containing 12 mol% cerium oxide and a primary particle size of 85 nm, and the commercially available Cr5B3 powder with a primary particle size of 57 nm were added to anhydrous ethanol in a weight ratio of 70:10:20, mixed evenly on a ball mill, then poured on a white porcelain plate, and dried in an oven at 100°C. The dried mixed powder was spray granulated to obtain 500 g of granulated powder with an average particle size of 60 µm, which was isostatically pressed under a pressure of 200 MPa, and then heated to 1550°C at a rate of 2°C / min in a high-temperature furnace in an air atmosphere and kept warm for 2 hours. After cooling to 600°C at a rate of 3°C / min and furnace cooling to room temperature, a zirconium oxide composite ceramic with a density of 98.1% of the theoretical density was obtained.
[0044] X-ray diffraction analysis of the zirconia composite ceramic showed that it was composed of zirconia crystal phase and Cr5B3 crystal phase, in which the contents of monoclinic and tetragonal zirconia in the zirconia crystal phase were 0.6vol% and 99.4vol%, respectively. Analysis under SEM (scanning electron microscope) showed that the grain size of Y-TZP in the zirconia composite ceramic was 0.63µm, the grain size of Ce-TZP was 2.4µm, and the grain size of Cr5B3 was 2.4µm.
[0045] After analysis, the hardness of the composite ceramic is 12.3Gpa and the fracture toughness is 7.6Mpa.m 1 / 2 After the zirconia composite ceramic was hydrothermally treated at 134°C in water vapor at a pressure of 0.2 MPa for 20 h, the crystal phase composition of the zirconia composite ceramic was analyzed by X-ray diffraction, and it was found that it was composed of zirconia crystal phase and Cr5B3 crystal phase, wherein the contents of monoclinic and tetragonal zirconia in the zirconia crystal phase were 4.5 vol% and 95.5 vol%, respectively.
[0046] Example 6 Preparation of zirconium oxide composite ceramic 6
[0047] The commercially available Y-TZP powder containing 3 mol% yttrium oxide and a primary particle size of 90 nm, the commercially available Ce-TZP powder containing 12 mol% cerium oxide and a primary particle size of 85 nm, and the commercially available Cr5B3 powder with a primary particle size of 57 nm were added to anhydrous ethanol in a weight ratio of 70:15:15, mixed evenly on a ball mill, then poured on a white porcelain plate, and dried in an oven at 100°C. The dried mixed powder was spray granulated to obtain 500 g of granulated powder with an average particle size of 60 µm, which was isostatically pressed under a pressure of 200 MPa, and then heated to 1550°C at a rate of 2°C / min in a high-temperature furnace in an air atmosphere and kept warm for 2 hours. After cooling to 600°C at a rate of 3°C / min and furnace cooling to room temperature, a zirconium oxide composite ceramic with a density of 98.2% of the theoretical density was obtained.
[0048] X-ray diffraction analysis of the zirconia composite ceramic showed that it was composed of zirconia crystal phase and Cr5B3 crystal phase, in which the contents of monoclinic and tetragonal zirconia in the zirconia crystal phase were 0.8 vol% and 99.2 vol%, respectively. Under SEM (scanning electron microscope), the grain size of Y-TZP in the zirconia ceramic was 0.64 µm, the grain size of Ce-TZP was 2.3 µm, and the grain size of Cr3B5 was 2.5 µm. After analysis, the hardness of the composite ceramic was 11.7 Gpa and the fracture toughness was 8.2 Mpa.m 1 / 2 After the zirconia composite ceramic was hydrothermally treated at 134°C in water vapor at a pressure of 0.2 MPa for 20 h, the crystal phase composition of the zirconia composite ceramic was analyzed by X-ray diffraction, and it was found that it was composed of zirconia crystal phase and Cr5B3 crystal phase, wherein the contents of monoclinic and tetragonal zirconia in the zirconia crystal phase were 7.0 vol% and 93.0 vol%, respectively.
[0049] Comparative Example 1 Preparation of Zirconia Ceramic 1
[0050] Take commercially available Y-TZP powder containing 3 mol% yttrium oxide and a primary particle size of 90 nm, and after spray granulation, obtain 500 g of granulated powder with an average particle size of 60 µm, which is isostatically pressed under a pressure of 200 MPa, and then heated to 1500 ° C at a rate of 2 ° C / min in a high-temperature furnace in an air atmosphere and kept warm for 2 h, cooled to 600 ° C at a rate of 3 ° C / min and furnace cooled to room temperature, to obtain a zirconia ceramic with a density of 99.5% of the theoretical density.
[0051] X-ray diffraction analysis shows that the monoclinic and tetragonal zirconium oxide contents in the zirconium oxide ceramic are 3.0 vol% and 97.0 vol%, respectively. SEM (scanning electron microscope) analysis shows that the grain size of zirconium oxide in the zirconium oxide ceramic is 0.65 µm. Analysis shows that the hardness of the ceramic is 10.5 Gpa and the fracture toughness is 8.2 Mpa.m1 / 2 After the zirconia ceramic was hydrothermally treated at 134° C. in water vapor at a pressure of 0.2 MPa for 20 h, X-ray diffraction analysis showed that the contents of monoclinic and tetragonal zirconia in the zirconia ceramic were 60.2 vol% and 39.8 vol%, respectively.
[0052] Comparative Example 2 Preparation of Zirconia Ceramic 2
[0053] The commercially available Y-TZP powder containing 3 mol% yttrium oxide and a primary particle size of 90nm and the commercially available Ce-TZP powder containing 12 mol% cerium oxide and a primary particle size of 85nm were added to anhydrous ethanol at a weight ratio of 95:5, mixed evenly on a ball mill, then poured on a white porcelain plate and dried in an oven at 100°C. The dried mixed powder was spray granulated to obtain 500g of granulated powder with an average particle size of 60µm, which was isostatically pressed under a pressure of 200MPa, and then heated to 1500°C at a rate of 2°C / min in a high-temperature furnace in an air atmosphere and kept warm for 2h. After cooling to 600°C at a rate of 3°C / min and furnace cooling to room temperature, a zirconia ceramic with a density of 99.3% of the theoretical density was obtained.
[0054] X-ray diffraction analysis shows that the monoclinic and tetragonal zirconium oxide contents in the zirconia ceramic are 2.8 vol% and 97.2 vol%, respectively. SEM (scanning electron microscope) analysis shows that the grain size of Y-TZP in the zirconia ceramic is 0.65 µm, and the grain size of Ce-TZP is 2.5 µm. The hardness of the ceramic is 10.5 Gpa, and the fracture toughness is 8.4 Mpa.m 1 / 2 The zirconia ceramic was hydrothermally treated at 134° C. in water vapor at a pressure of 0.2 MPa for 20 h. X-ray diffraction analysis showed that the contents of monoclinic and tetragonal zirconia in the zirconia ceramic were 57.0 vol% and 43.0 vol%, respectively.
[0055] Comparative Example 3 Preparation of Zirconia Composite Ceramic 7
[0056] The commercially available Y-TZP powder containing 3 mol% yttrium oxide and a primary particle size of 90 nm and the commercially available Cr3B5 powder with a primary particle size of 57 nm were added to anhydrous ethanol at a weight ratio of 95:5, mixed evenly on a ball mill, then poured onto a white porcelain plate and dried in an oven at 100°C. The dried mixed powder was spray granulated to obtain 500 g of granulated powder with an average particle size of 62 µm, which was isostatically pressed at a pressure of 200 MPa, and then heated to 1550°C at a rate of 2°C / min in a high-temperature furnace in an air atmosphere and kept warm for 2 hours, cooled to 600°C at a rate of 3°C / min and furnace cooled to room temperature, and a zirconium oxide composite ceramic with a density of 98.3% of the theoretical density was obtained.
[0057] X-ray diffraction analysis of the crystal phase composition of the composite ceramic revealed that it is composed of zirconium oxide crystal phase and Cr5B3 crystal phase, wherein the contents of monoclinic and tetragonal zirconium oxide in the zirconium oxide crystal phase are 2.2 vol% and 97.8 vol%, respectively. Analysis under SEM (scanning electron microscope) showed that the grain size of Y-TZP in the zirconium oxide ceramic is 0.70 µm, and the grain size of Cr3B5 is 2.8 µm. Analysis showed that the hardness of the composite ceramic is 10.9 Gpa, and the fracture toughness is 8.0 Mpa.m 1 / 2 After the zirconia ceramic was hydrothermally treated at 134°C in water vapor at a pressure of 0.2 MPa for 20 hours, the crystal phase composition of the composite ceramic was analyzed by X-ray diffraction, and it was found that it was composed of zirconia crystal phase and Cr5B3 crystal phase, among which the contents of monoclinic and tetragonal zirconia in the zirconia crystal phase were 45.3 vol% and 54.7 vol%, respectively.
[0058] Comparative Example 4 Preparation of Zirconia Composite Ceramic 8
[0059] The commercially available Y-TZP powder containing 3 mol% yttrium oxide and a primary particle size of 90 nm and the commercially available Cr5B3 powder with a primary particle size of 57 nm were added to anhydrous ethanol at a weight ratio of 90:10, mixed evenly on a ball mill, then poured on a white porcelain plate and dried in an oven at 100°C. The dried mixed powder was spray granulated to obtain 500g of granulated powder with an average particle size of 60µm, which was isostatically pressed at a pressure of 200MPa, and then heated to 1550°C at a rate of 2°C / min in a high-temperature furnace in an air atmosphere and kept warm for 2h. After cooling to 600°C at a rate of 3°C / min and furnace cooling to room temperature, a zirconium oxide composite ceramic with a density of 98.5% of the theoretical density was obtained.
[0060] X-ray diffraction analysis of the zirconia composite ceramic found that it was composed of zirconia crystal phase and Cr5B3 crystal phase, in which the monoclinic and tetragonal zirconia contents in the zirconia crystal phase were 1.2 vol% and 98.8 vol%, respectively. Under SEM (scanning electron microscope), the grain size of Y-TZP in the zirconia ceramic was 0.70 µm, and the grain size of Cr5B3 was 2.7 µm. After analysis, the hardness of the composite ceramic was 11.2 Gpa and the fracture toughness was 7.7 Mpa.m 1 / 2 After the zirconia ceramic was hydrothermally treated at 134°C in water vapor at a pressure of 0.2 MPa for 20 h, the crystal phase composition of the zirconia composite ceramic was analyzed by X-ray diffraction, and it was found that it was composed of zirconia crystal phase and Cr5B3 crystal phase, wherein the contents of monoclinic and tetragonal zirconia in the zirconia crystal phase were 15.4 vol% and 84.6 vol%, respectively.
[0061] Comparative Example 5 Preparation of Zirconia Ceramic 3
[0062] The commercially available Y-TZP powder containing 3 mol% yttrium oxide and a primary particle size of 90 nm and the commercially available Ce-TZP powder containing 12 mol% cerium oxide and a primary particle size of 85 nm were added to anhydrous ethanol at a weight ratio of 90:10, mixed evenly on a ball mill, then poured on a white porcelain plate and dried in an oven at 100°C. The dried mixed powder was spray granulated to obtain 500g of granulated powder with an average particle size of 60µm, which was isostatically pressed under a pressure of 200MPa, and then heated to 1500°C at a rate of 2°C / min in a high-temperature furnace in an air atmosphere and kept warm for 2h. After cooling to 600°C at a rate of 3°C / min and furnace cooling to room temperature, a zirconia ceramic with a density of 99.1% of the theoretical density was obtained.
[0063] X-ray diffraction analysis shows that the monoclinic and tetragonal zirconium oxide contents in the zirconia ceramic are 2.7 vol% and 97.3 vol%, respectively. SEM (scanning electron microscope) analysis shows that the grain size of Y-TZP in the zirconia ceramic is 0.65 µm, and the grain size of Ce-TZP is 2.5 µm. The hardness of the ceramic is 10.5 Gpa, and the fracture toughness is 8.6 Mpa.m 1 / 2 After the zirconia ceramic was hydrothermally treated at 134° C. in water vapor at a pressure of 0.2 MPa for 20 h, X-ray diffraction analysis showed that the contents of monoclinic and tetragonal zirconia in the zirconia ceramic were 54.5 vol% and 45.5 vol%, respectively.
[0064] Comparative Example 6 Preparation of Zirconia Composite Ceramic 9
[0065] The commercially available Y-TZP powder containing 3 mol% yttrium oxide and a primary particle size of 90 nm and the commercially available Cr5B3 powder with a primary particle size of 57 nm were added to anhydrous ethanol at a weight ratio of 85:15, mixed evenly on a ball mill, then poured on a white porcelain plate and dried in an oven at 100°C. The dried mixed powder was spray granulated to obtain 500g of granulated powder with an average particle size of 60µm, which was isostatically pressed under a pressure of 200MPa, and then heated to 1550°C at a rate of 2°C / min in a high-temperature furnace in an air atmosphere and kept warm for 2h. After cooling to 600°C at a rate of 3°C / min and furnace cooling to room temperature, a zirconium oxide composite ceramic with a density of 98.2% of the theoretical density was obtained.
[0066] X-ray diffraction analysis of the zirconia composite ceramic found that it was composed of zirconia crystal phase and Cr5B3 crystal phase, in which the monoclinic and tetragonal zirconia contents in the zirconia crystal phase were 1.0 vol% and 99.0 vol%, respectively. Under SEM (scanning electron microscope), the grain size of Y-TZP in the zirconia composite ceramic was 0.70 µm, and the grain size of Cr5B3 was 2.7 µm. After analysis, the hardness of the composite ceramic was 11.7 Gpa and the fracture toughness was 7.5 Mpa.m 1 / 2 After the zirconia composite ceramic was hydrothermally treated at 134°C in water vapor at a pressure of 0.2 MPa for 20 h, the crystal phase composition of the zirconia composite ceramic was analyzed by X-ray diffraction, and it was found that it was composed of zirconia crystal phase and Cr5B3 crystal phase, wherein the contents of monoclinic and tetragonal zirconia in the zirconia crystal phase were 9.0 vol% and 91.0 vol%, respectively.
[0067] Comparative Example 7 Preparation of Zirconia Composite Ceramic 10
[0068] The commercially available Y-TZP powder containing 3 mol% yttrium oxide and a primary particle size of 90 nm and the commercially available Cr5B3 powder with a primary particle size of 57 nm were added to anhydrous ethanol at a weight ratio of 80:20, mixed evenly on a ball mill, then poured on a white porcelain plate and dried in an oven at 100°C. The dried mixed powder was spray granulated to obtain 500g of granulated powder with an average particle size of 60µm, which was isostatically pressed at a pressure of 200MPa, and then heated to 1550°C at a rate of 2°C / min in a high-temperature furnace in an air atmosphere and kept warm for 2h. After cooling to 600°C at a rate of 3°C / min and furnace cooling to room temperature, a zirconium oxide composite ceramic with a density of 98.5% of the theoretical density was obtained.
[0069] X-ray diffraction analysis of the zirconia composite ceramic found that it was composed of zirconia crystal phase and Cr5B3 crystal phase, in which the monoclinic and tetragonal zirconia contents in the zirconia crystal phase were 0.8 vol% and 99.2 vol%, respectively. Under SEM (scanning electron microscope), the grain size of Y-TZP in the zirconia ceramic was 0.71 µm, and the grain size of Cr5B3 was 2.7 µm. After analysis, the hardness of the composite ceramic was 12.3 Gpa and the fracture toughness was 7.2 Mpa.m 1 / 2 After the zirconia ceramic was hydrothermally treated at 134°C in water vapor at a pressure of 0.2 MPa for 20 h, the crystal phase composition of the zirconia composite ceramic was analyzed by X-ray diffraction, and it was found that it was composed of zirconia crystal phase and Cr5B3 crystal phase, wherein the contents of monoclinic and tetragonal zirconia in the zirconia crystal phase were 5.0 vol% and 95.0 vol%, respectively.
[0070] Comparative Example 8 Preparation of Zirconia Composite Ceramic 11
[0071] The commercially available Y-TZP powder containing 3 mol% yttrium oxide and a primary particle size of 90 nm and the commercially available Cr5B3 powder with a primary particle size of 57 nm were added to anhydrous ethanol at a weight ratio of 70:30, mixed evenly on a ball mill, then poured on a white porcelain plate and dried in an oven at 100°C. The dried mixed powder was spray granulated to obtain 500g of granulated powder with an average particle size of 60µm, which was isostatically pressed at a pressure of 200MPa, and then heated to 1550°C at a rate of 2°C / min in a high-temperature furnace in an air atmosphere and kept warm for 2h. After cooling to 600°C at a rate of 3°C / min and furnace cooling to room temperature, a zirconium oxide composite ceramic with a density of 98.4% of the theoretical density was obtained.
[0072] X-ray diffraction analysis of the zirconia composite ceramic revealed that it consisted of zirconia crystal phase and Cr5B3 crystal phase, wherein the contents of monoclinic and tetragonal zirconia in the zirconia crystal phase were 0 vol% and 100 vol%, respectively.
[0073] Under SEM (scanning electron microscope) analysis, the grain size of Y-TZP in the zirconia composite ceramic is 0.70µm, and the grain size of Cr5B3 is 2.7µm. After analysis, the hardness of the composite ceramic is 13.2Gpa and the fracture toughness is 6.6Mpa.m 1 / 2 After the zirconia composite ceramic was hydrothermally treated at 134°C in water vapor at a pressure of 0.2 MPa for 20 h, the crystal phase composition of the zirconia composite ceramic was analyzed by X-ray diffraction, and it was found that it was composed of zirconia crystal phase and Cr5B3 crystal phase, wherein the contents of monoclinic and tetragonal zirconia in the zirconia crystal phase were 3.0 vol% and 97.0 vol%, respectively.
[0074] Table 1 Performance analysis of ceramics prepared in Examples 1-6 and Comparative Examples 1-8
[0075]
[0076] By comparing comparative examples 1, 3, 4, 6, 7 and 8, it can be found that when Y-TZP and Cr5B3 form a composite ceramic, with the increase of Cr5B3 content, the ability of zirconia ceramic in the composite ceramic to resist hydrothermal aging phase transformation is enhanced, and the content of monoclinic phase generated after aging treatment for 20 hours is small. At the same time, the surface hardness is improved, but the fracture toughness is significantly reduced.
[0077] From the test results of Examples 3, 4, 5 and 6, in the composite ceramics formed by Y-TZP, Ce-TZP and Cr5B3, with the addition of Ce-TZP, the fracture toughness of the composite ceramics is restored, while maintaining the excellent hydrothermal aging phase transformation resistance and high hardness brought by the Cr5B3 crystal phase. Therefore, the composite ceramics have excellent hydrothermal aging phase transformation resistance (that is, after 20 hours of hydrothermal aging treatment, very little tetragonal phase is transformed into monoclinic phase), high hardness and high fracture toughness, and are the preferred embodiment of the present invention.
[0078] As described above, the zirconia composite ceramic of the present invention has excellent comprehensive properties, and therefore has a wide range of applications, including but not limited to industrial fields (such as plungers, etc.) and medical fields (such as artificial joints, etc.).
[0079] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A zirconium oxide composite ceramic, characterized in that: The composite ceramic consists of 5-30wt% of pentachromium triboride, 5-15wt% of Ce-TZP and the balance of Y-TZP.
2. The zirconia composite ceramic according to claim 1, characterized in that: The composite ceramic consists of 5-20wt% of pentachromium triboride, 5-15wt% of Ce-TZP and the balance of Y-TZP.
3. The zirconia composite ceramic according to claim 2, characterized in that: The composite ceramic consists of 10-15wt% of pentachromium triboride, 10-15wt% of Ce-TZP and the balance of Y-TZP.
4. The zirconia composite ceramic according to claim 3, characterized in that: The composite ceramic consists of 12-15wt% of pentachromium triboride, 12-15wt% of Ce-TZP and the balance of Y-TZP.
5. A zirconia composite ceramic according to any one of claims 1 to 4, characterized in that: The grain size of the pentachromium triboride is 1.5-3.5 μm, the grain size of Ce-TZP is 1.0-5.0 μm, and the grain size of Y-TZP is 0.4-0.8 μm.
6. The zirconia composite ceramic according to claim 5, characterized in that: The grain size of the pentachromium triboride is 2.5-3.5 μm, the grain size of Ce-TZP is 1.0-3.0 μm, and the grain size of Y-TZP is 0.5-0.7 μm.
Citation Information
Patent Citations
Heat-stability-resistant high toughness ceramic sintered body and manufacture
JP1987046959A